1960
DOI: 10.1111/imj.1960.9.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Casual Arterial Pressure of Fijians and Indians in Fiji

Abstract: Summary Casual arterial blood pressure has been measured in population samples of Fijians and Indians inhabiting Fiji. Certain features of blood pressure found in peoples of Europe and America have been found in both races. The means and standard deviations of systolic pressures rise with age. The means of diastolic pressures rise, at least to the sixth decade. Pressures rise more in females than in males. Frequency distributions of pressures are continuous and mostly show positive skewness. Each race contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Previous population studies of BP in Fiji dating back to the 1950s have identified an association between increasing age and increases in BP means and hypertension prevalence in both sexes and ethnicities [ 15 , 16 , 21 , 23 ]. Increased BP with increasing age has also been found in other Pacific Islands, including Samoa [ 24 ] and Tonga [ 25 ], and elsewhere, including Australia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous population studies of BP in Fiji dating back to the 1950s have identified an association between increasing age and increases in BP means and hypertension prevalence in both sexes and ethnicities [ 15 , 16 , 21 , 23 ]. Increased BP with increasing age has also been found in other Pacific Islands, including Samoa [ 24 ] and Tonga [ 25 ], and elsewhere, including Australia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several BP surveys undertaken in Fiji were not included in the current analysis because they measured BP in one sex only [ 15 ], in a specific and often narrow age group [ 15 , 16 ], one ethnicity only [ 15 – 20 ], in an exclusive or undefined urban/rural population [ 15 , 18 – 21 ], or survey results were only available as a broad summary [ 22 ]. These surveys were excluded because they were not nationally representative, and it was not possible to adjust their data to the nearest previous census (by age, ethnicity, and rural/urban distributions for each sex).…”
Section: Methodsmentioning
confidence: 99%
“…Relatively high prevalences of NCD and RFs in Fiji were documented by population NCD and RF surveys from the 1960s [ 17 ] and 1980s [ 18 ], as well as the WHO NCD Fiji STEPs surveys 2002 and 2011 [ 8 , Fiji MoH, Fiji NCD STEPS Survey 2011 unit record data supplied 2014, unpublished]. Studies of trends over 30 years (to 2011) in diabetes and obesity [ 19 ], and in mean BP & HT [ 20 ] from population surveys in Fiji indicate continued increases in these RFs, commensurate with trends in premature adult mortality and proportional mortality from CVD [ 1 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also to Beecham Research Laboratories for the supplies of methicillin used in the earlier cases. We have recently reported measurements of bloodpressure in population samples in Fiji and in the Gilbert Islands (Lovell et al, 1960;Maddocks, 1961). During these surveys the opportunity was taken to study body temperature.…”
Section: Discussionmentioning
confidence: 99%